2018
DOI: 10.3389/fmicb.2018.02958
|View full text |Cite|
|
Sign up to set email alerts
|

Sho1 and Msb2 Play Complementary but Distinct Roles in Stress Responses, Sexual Differentiation, and Pathogenicity of Cryptococcus neoformans

Abstract: The high-osmolarity glycerol response (HOG) pathway is pivotal in environmental stress response, differentiation, and virulence of Cryptococcus neoformans, which causes fatal meningoencephalitis. A putative membrane sensor protein, Sho1, has been postulated to regulate HOG pathway, but its regulatory mechanism remains elusive. In this study, we characterized the function of Sho1 with relation to the HOG pathway in C. neoformans. Sho1 played minor roles in osmoresistance, thermotolerance, and maintenance of mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Many recent studies of Sho1 orthologs in fungi have demonstrated that Sho1 plays a critical role in pathogenesis, and this role may overlap with the signal transducing roles of other surface sensors (Msb2, Sln1, etc.) (Lanver et al, 2010;Zhang et al, 2010;Liu et al, 2011;Gu et al, 2015;Perez-Nadales and Di Pietro, 2015;So et al, 2018;Ren et al, 2019). For instance, FgSho1 and FgSln1 have an additive effect on the pathogenicity of F. graminearum on wheat (Gu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies of Sho1 orthologs in fungi have demonstrated that Sho1 plays a critical role in pathogenesis, and this role may overlap with the signal transducing roles of other surface sensors (Msb2, Sln1, etc.) (Lanver et al, 2010;Zhang et al, 2010;Liu et al, 2011;Gu et al, 2015;Perez-Nadales and Di Pietro, 2015;So et al, 2018;Ren et al, 2019). For instance, FgSho1 and FgSln1 have an additive effect on the pathogenicity of F. graminearum on wheat (Gu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The interesting exception to this is responses to osmotic stress, as osmotic stress-induced dephosphorylation of Hog1 and resistance to this stress are Ssk1-independent (Bahn et al, 2006). This suggests the existence of an additional two-component independent pathway that relays osmotic stress signals to Hog1 but, in contrast to S. cerevisiae , this is not governed by the Sho1/Msb2 pathway (So et al, 2018). As in S. cerevisiae , deletion of the Ypd1 phosphorelay protein gives a lethal phenotype in C. neoformans and this is dependent on Hog1 presence (Lee et al, 2011).…”
Section: Cryptococcus Neoformans Hog1mentioning
confidence: 99%
“… C. albicans Msb2p is a global regulator of temperature stress ( 46 ), while OPY2 mutants display susceptibility to CR, but it did not play a role in the adaptation to high osmolarity or oxidative stress and virulence in the Galleria mellonella model ( 47 ). Sho1 and Msb2 homologues play complementary but distinct roles in stress responses, differentiation, and pathogenicity of the human pathogen Cryptococcus neoformans ( 48 ). In the dimorphic plant-pathogenic fungus Ustilago maydis , Sho1 and Msb2-like proteins play a key role during appressorium differentiation and are involved in plant surface sensing ( 49 ).…”
Section: Discussionmentioning
confidence: 99%